THE IMPACT OF SMARTPHONE SHARING ON STUDENT LEARNING ACHIEVEMENT AT SMA NEGERI 1 GIDO - Adrianus Bawamenewi; Anugerah Tatema Harefa; Oktorius Berkat Jaya Zega (Jurnal Scientia, 2023)
This study aims to determine the impact of smartphone sharing on student learning achievement and the efforts and obstacles faced over smartphone sharing on student learning achievement. This research uses a qualitative method with a descriptive approach. Data collection techniques through interviews, observation, and documentation. The results of the study concluded that the impact of smartphone sharing on student learning achievement is that teachers and students are facilitated to be able to communicate via smartphones in following and discussing learning, especially during face-to-face restrictions at school, the use of smartphones greatly supports the Teaching and Learning Activities process. In addition, the distribution of smartphones in addition to supporting the learning process can also develop themselves outside of school by looking for references and information on the internet. Efforts made on the impact of smartphone distribution are teachers controlling students in using smartphones during face-to-face learning, cooperation between parents and teachers to jointly supervise students in the use of smartphones when students are outside school, providing opportunities for students who at the time of sending assignments do not have data packages can directly submit offline. The obstacles faced in the distribution of smartphones are student unawareness of the proper use of smartphones, teachers as humans have limitations to supervise students optimally, internet networks and also the cost of purchasing data packages are an obstacle, because not all students have the same economic ability to buy internet data packages.